Reorienting Ecological Paradigm for Harmonization of Humans and Nature: A Christian Perspective - Johanna Silvana Talupun; Eklepinus Jefry Sopacuaperu (Graduate Program of Pontianak Institute of Islamic Studies, 2022)
The ecological crisis that is very alarming at the moment is caused by, among others, the “poor” ethics in the relationship between humans and the universe. Humans tend to see themselves as high and mighty, also the most decisive (superior). Conversely, nature is perceived as less important, of lower class, not human (inferior). Inequality in the relationship between humans and nature has further wosened the “ethical poverty” and the relationship is increasingly immoral. Thus, ethical poverty forms paradigm disorientation, dysfunction of action and disintegration of relations. Therefore, this article aims to reorient the paradigm, and to encourage the creation of harmonious relations based on a paradigm shift in favor of life. Everything begins with a search for social ethics that observes the events of the ecological crisis, investigates in-depth and hears various calls for a paradigm shift, identifies ethical-ecological principles and seeks a hermeneutical-biblical ethics as a religious interpretation that goes beyond the anthropocentrism of interpreting the holy scriptures. The method used in this research is a literature study. Data related to the issue of the ecological crisis was collected and then an in-depth analysis was carried out and finally conclusions were made. The issue of ecological crisis used as a reference in this research is the case of mining on Romang Island. This case is analyzed with a social ethics and a religious ethics approaches. The results of the analysis serve as a reference for transformative actions.